"Lifestyle of a Traditional Family of Past and Present Taken from Information of Johanna Cornect" - Foley, Margaret Elizabeth (1990)
Dissertation trimestrielle d'étudiant(e) en folklore à l'Université Memorial. -- Memorial University folklore student term paper.